Determining the ecological security pattern and important ecological regions based on the supply–demand of ecosystem services: A case study of Xuzhou City, China - Wang, Ziyi; Zhang, Ji; Chen, Jiangchang; Gao, Huizhi; Li, Jiaming; Li, Muhan (Frontiers in Public Health, 2023)
The supply–demand for ecosystem services (ESs) is the bridge between ecological security patterns (ESPs) and human wellbeing. This study proposed a research framework of ESP of “supply–demand–corridor–node” and took Xuzhou, China, as a research case, providing a new perspective for the construction of ESPs. The framework was divided into four sections: identifying the ecological source based on the ESs supply; utilizing multi-source economic-social data to characterize the demand of ESs and constructing a resistance surface; defining the ecological corridor in the study area by employing the Linkage Mapper; and identifying crucial ecological protection/restoration areas along the ecological corridor. The results showed that the area of the supply source of ESs in Xuzhou City is 573.89 km2, accounting for 5.19% of the city's total area. The spatial distribution of 105 ecological corridors revealed that there were multiple and dense ecological corridors in the middle of the city, but few in the northwest and southeast. A total of 14 ecological protection areas were located primarily in the south of the urban area, and 10 ecological restoration areas were located primarily in the middle and north of the urban area, with a total area of 4.74 km2. The findings of this article will be useful in developing ESPs and determining important ecological protection/restoration areas in Xuzhou, China. The research framework could potentially be used in other areas.